Sources of Exchange Rate Fluctuations in Thailand - Siriwutiset, Trin (2006)
Exchange rate fluctuations play an important role in economic decision. The rise or falls in exchange rate are one of the most concerned issue in macroeconomics. This study aims to identify the sources of exchange rate fluctuations of the Thai Baht from various types of shocks between 1997:09 and 2002:08 by using VAR (Vector Autoregressive) model.